Wednesday

April 23, 2014

April 23, 2014

Posted by **Scotty** on Sunday, February 13, 2011 at 12:21am.

11x-37=x+23

10p-26=p-44

-13x+5=4x-6

-7x+13=4x-7

11x+5=17

-11x+13=-42

-15y+26=-19

5x-13=9x+15

6q-14=11q-19

4(-2x-5)=29

12(2-5x)=(3x-1)

9x+2=15x-10

19q+4=7q-3

6(2x+1)=9(2x+6)

-7(x-3)=8(4-5x)

-3(p-4)=8(4-9p)

-(y+15)=7(-5-3y)

6m+5=2m-6

7(2p-3)=5(6p-1)

-(y+12)=9(-7-2y)

-(x+7)=5(-11-5x)

7(2x+4)=28

-(y+12)=9(-7-2y)

-(x+7)=5(-11-5x)

7(2x+4)=28

5(-3x+2)=7

7p-3=2

-3(5p+2)=39

12x-15=21

8y+24=40

6x-15=22

-7(9y-5)=35

2(3x+4)=32

-12(7y-1)=12

4(5x+8)=-3

7(5q-2)=11(3-4q)

12(5x-7)=6(3x-14)

-(x+21)=6(-9-2x)

3(6x-5)=19x-2

6(7y-3)=43y-15

6(2-5x)=3(4-7x)

2(4-7y)=3(3-2y)

-(x-60)=5(12-7x)

7(4x-1)=12(3x-4)

8(2y-1)=12(3y-5)

-(x+40)=10(3x-4)

- Math -
**Bosnian**, Sunday, February 13, 2011 at 4:30amDo mathematical operations,then put unknown values on left side of equation,nubers on right side.

For example:

-(x+40)=10(3x-4)

-x-40=30x-40

-x-30x=-40+40

-29x=0

x=0

-11x+13=-42

-11x=-42-13

-11x=55 Divide with -11

x= -5

9x+2=15x-10

9x-15x= -10-2

-6x= -12 Divide with -6

x=(-12)/(-6)=2

2(4-7y)=3(3-2y)

8-14y=9-6y

-14y+6y=9-8

-8y=1 Divide with -8

y= -1/8

**Related Questions**

Urgent Math please check - Very Important I can get someone to check these for ...

Polynomial- Doublecheck2 - I asked this earlier, but I didn't get an answer. I'm...

Algebra 1b! - 1. Find the excluded value of x for the polynomomial expression ...

Algebra - Can someone check my algebra answers and help me with the problems I ...

Algebra - The answer in the book however says -(5x^2-17x-9)/(x-3)(x+2) so I don'...

Algebra - (x)/(x-3)-4-(2x-5)/(x+2) I posted something before this, so now this ...

Algebra - (x)/(x-3)-4-(2x-5)/(x+2) I posted something before this, so now this ...

math - can you check my answers? i have to write the clop intercept form of the ...

algebra - can you check my answers? i have to write the slope intercept form of ...

ALGEBRA - 1, Factor each expression x^2 - 10x - 24 A. (x + 4)(x - 6) B. (x + 6)(...